Effects of Planting Herbal Plants by Using Recyclable Empty Bottles in Grade 12 ABM Strand Students in Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This research focused on the effects of planting herbal plants by using recyclable plastic bottles and make it a “paso” to be planted that will help improve the cleanliness of our environment. This paper discussed the effects of planting a herbal plant by using recyclable plastic bottles on Grade 12 Accountancy, Business, and Management (ABM) Strandstudents at Bestlink College of the Philippines. Nowadays, our environment has many wastes, especially plastic bottles that get stuck in the drainage, thereby causing flooding in our community. Thus, we should know how we can help our community by convincing students to plant again by using recyclable plastic bottles. To help the environment, the plants that we planted are herbal plants; we can use those plants that we planted. The objective of this research was to lessen the number of plastic bottles by making a recyclable “paso.” Hence, students should know the benefits of planting plants by using empty plastic bottles at Bestlink College of the Philippines. This research also aimed to maintain clean surroundings in Bestlink College of the Philippines. This study used descriptive design and qualitative research. This research involved 50 selected grade 12 ABM students. A total of 11 variables, such as environmental cleanliness, proper use of plastic bottles by using it for planting, improved air quality by planting a herbal plant that is more useful than an ordinary plant, treatment of skin diseases by using a herbal plant, improve the ambiance of the environment, and prevent students from contacting diseases from the environment, were considered to determine the effects of planting herbal plants by using recyclable plastic bottles. The results of this study revealed that planting medicinal plants in recyclable plastic bottles can lessen the number of plastic bottles in the surroundings, cure some diseases by using the medicinal plants that were planted, and improve the ambiance of our environment. Hence, the students will know the importance of recycling plastic bottles and planting medicinal plants.
Keywords: herbal plants, plastic bottles, recyclable